2013
DOI: 10.1371/journal.pone.0054635
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Electrophysiological Gene Expression in Failing and Non-Failing Human Hearts

Abstract: The increasing availability of human cardiac tissues for study are critically important in increasing our understanding of the impact of gender, age, and other parameters, such as medications and cardiac disease, on arrhythmia susceptibility. In this study, we aimed to compare the mRNA expression of 89 ion channel subunits, calcium handling proteins, and transcription factors important in cardiac conduction and arrhythmogenesis in the left atria (LA) and ventricles (LV) of failing and nonfailing human hearts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 60 publications
4
53
0
3
Order By: Relevance
“…Accordingly, a current gradient is observed from subepicardium (more I TO ) to subendocardium (less I TO ) (Gaborit et al, 2007;Nabauer et al, 1996;Zicha et al, 2004). Additional genes are observed to be differentially expressed along the transmural plane such as those encoding I Ks (KCNQ1, KCNE1) and I Kr (KCNH2, KCNE2) channels, whereby epicardial expression predominates, although this may be gender dependent (Ambrosi et al, 2013;Gaborit et al, 2007;Holzem et al, 2016). These expression gradients are in line with the observed shorter action potentials of myocytes from subepicardium compared to subendocardium in both isolated myocytes (Nabauer et al, 1996) as well as in the intact ventricular wall (Fig.…”
Section: Transmural Gene Expressionsupporting
confidence: 66%
“…Accordingly, a current gradient is observed from subepicardium (more I TO ) to subendocardium (less I TO ) (Gaborit et al, 2007;Nabauer et al, 1996;Zicha et al, 2004). Additional genes are observed to be differentially expressed along the transmural plane such as those encoding I Ks (KCNQ1, KCNE1) and I Kr (KCNH2, KCNE2) channels, whereby epicardial expression predominates, although this may be gender dependent (Ambrosi et al, 2013;Gaborit et al, 2007;Holzem et al, 2016). These expression gradients are in line with the observed shorter action potentials of myocytes from subepicardium compared to subendocardium in both isolated myocytes (Nabauer et al, 1996) as well as in the intact ventricular wall (Fig.…”
Section: Transmural Gene Expressionsupporting
confidence: 66%
“…Custom-designed lowdensity Taqman gene arrays (Applied Biosystems, Foster City, CA) were then used to probe for the presence of 46 targets as previously described. 12 Genes selected for analysis included genes critical for glucose and fatty acid metabolism, mitochondrial function and regulation of energy metabolism, and are listed in Supplementary Table 2). Multiple comparisons statistical testing was conducted using the false discovery rate (FDR) method, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in most species (human, canine, rabbit, rat and mouse ) it has been found that the Kv4.3 gene is expressed uniformly across the ventricle wall (Abd Allah et al, 2012; Ambrosi et al, 2013; Calloe et al, 2010; Dixon et al, 1996; Gaborit et al, 2007; Goltz et al, 2007; Huang et al, 2001; Liu et al, 2015; Radicke et al, 2006; Rosati et al, 2003; Rosati et al, 2001; Soltysinska et al, 2009). One exception is a report that Kv4.3 mRNA and protein are expressed in an epicardial to endocardial gradient in ferret (Brahmajothi et al, 1999).…”
Section: Molecular Basis Of Ito and Its Transmural Gradient Of Expresmentioning
confidence: 95%
“…KChIP2 mRNA is expressed in a steep transmural gradient across the left ventricle in human, canine, ferret and rabbit, in parallel with I to expression in these species (Abd Allah et al, 2012; Ambrosi et al, 2013; Calloe et al, 2010; Gaborit et al, 2007; Patel et al, 2002; Radicke et al, 2006; Rosati et al, 2003; Rosati et al, 2001; Soltysinska et al, 2009; Zicha et al, 2004). There is correspondingly steep gradient in KChIP2 protein across the human and canine ventricles (Patel and Campbell, 2005; Rosati et al, 2003; Zicha et al, 2004).…”
Section: Molecular Basis Of Ito and Its Transmural Gradient Of Expresmentioning
confidence: 96%